Preconception micronutrient supplementation with iron and folic acid compared with folic acid alone affects linear growth and fine motor development at 2 years of age: A randomized controlled trial in Vietnam - Nguyen, Phuong Hong; Gonzalez-Casanova, Ines; Young, Melissa F.; Truong, Truong V.; Hoang, Hue; Nguyen, Huong; Nguyen, Son; DiGirolamo, Ann M.; Martorell, Reynaldo; Ramakrishnan, Usha (Elsevier, 2017)
Background Maternal health and nutrition play a crucial role in early child growth and development. However, little is known about the benefits of preconception micronutrient interventions beyond the role of folic acid (FA) and neural tube defects. Objective We evaluated the impact of weekly preconception multiple micronutrient (MM) or iron and folic acid (IFA) supplementation on child growth and development through the age of 2 y compared with FA alone. Methods We followed 1599 offspring born to women who participated in a randomized controlled trial of preconception supplementation in Vietnam. Women received weekly supplements that contained either 2800 μg FA, 60 mg Fe and 2800 μg FA, or 15 MMs including IFA, from baseline until conception followed by daily prenatal IFA supplements until delivery. Child anthropometry was measured at birth and at 3, 6, 12, 18, and 24 mo. Child development was measured with the use of the Bayley Scales for Infant Development III at 24 mo. Results The groups were similar for baseline maternal and offspring birth characteristics. At 24 mo of age, the offspring in the IFA group had significantly higher length-for-age z scores (LAZs) (0.14; 95% CI: 0.03, 0.26), reduced risk of being stunted (0.87; 95% CI: 0.76, 0.99), and smaller yearly decline in LAZs (0.10; 95% CI: 0.04, 0.15) than the offspring in the FA group. Similar trends were found for the offspring in the MM group compared with the FA group for LAZs (0.10; 95% CI: −0.02, 0.22) and the risk of being stunted (0.88; 95% CI: 0.77, 1.01). Offspring in the IFA group had improved motor development (P = 0.03), especially fine motor development (0.41; 95% CI: 0.05, 0.77), at the age of 24 mo, but there were no differences for measures of cognition or language. Conclusions Preconception supplementation with IFA improved linear growth and fine motor development at 2 y of age compared with FA. Future studies should examine whether these effects persist and improve child health and schooling.